Unraveling the influence of TTF-1 expression on immunotherapy outcomes in PD-L1-high non-squamous NSCLC: a retrospective multicenter study - Nishioka, Naoya; Kawachi, Hayato; Yamada, Tadaaki; Tamiya, Motohiro; Negi, Yoshiki; Goto, Yasuhiro; Nakao, Akira; Shiotsu, Shinsuke; Tanimura, Keiko; Takeda, Takayuki; Okada, Asuka; Harada, Taishi; et al. (Frontiers in Immunology, 2024)
Several studies explored the association between thyroid transcription factor-1 (TTF-1) and the therapeutic efficacy of immunotherapy. However, the effect of TTF-1 on the therapeutic efficacy of programmed death-1 (PD-1) inhibitor/chemoimmunotherapy in patients with nonsquamous non-small cell lung cancer (non-Sq NSCLC) with a programmed death-ligand 1 (PD-L1) tumor proportion score of 50% or more who are highly susceptible to immunotherapy remains unresolved. Therefore, we evaluated whether TTF-1 has a clinical impact on this population.Patients with non-Sq NSCLC and high PD-L1 expression who received PD-1 inhibitor monotherapy or chemoimmunotherapy between May 2017 and December 2020 were retrospectively enrolled. Treatment efficacy was compared after adjusting for baseline differences using propensity score matching.Results: Among the 446 patients with NSCLC with high PD-L1 expression, 266 patients with non-Sq NSCLC were analyzed. No significant differences in therapeutic efficacy were observed between the TTF-1-positive and -negative groups in the overall and propensity score-matched populations. Of chemoimmunotherapy, pemetrexed containing regimen significantly prolonged progression-free survival compared to chemoimmunotherapy without pemetrexed, regardless of TTF-1 expression (TTF1 positive; HR: 0.46 (95% Confidence interval: 0.26-0.81), p<0.01, TTF-1 negative; HR: 0.29 (95% Confidence interval: 0.09-0.93), p=0.02).Discussion: TTF-1 expression did not affect the efficacy of PD-1 inhibitor monotherapy or chemoimmunotherapy in patients with non-Sq NSCLC with high PD-L1 expression. In this population, pemetrexed-containing chemoimmunotherapy demonstrated superior anti-tumor efficacy, irrespective of TTF-1 expression.